2017
DOI: 10.1136/acupmed-2016-011139
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Upregulates G Protein Coupled Activity in Samp8 Mice

Abstract: acupuncture attenuates cognitive deficits in a mouse model of AD via upregulation of G protein activity and stabilisation of the cellular signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…In the four rats models, intraperitoneal injection of scopolamine (SCO) was used to establish an AD model in one study [29] and intracerebroventricular (ICV) injection of Aβ 1-42 was used in two studies [34,35], and the ICV injection of Aβ 1-40 was used in the rest one study [38]. In mice models, three studies adopted APP/PS1 double transgenic mice model [28,33,39], and the rest used SAMP8 mice model as mentioned above [27,32,36,37,40].…”
Section: Model Preparation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the four rats models, intraperitoneal injection of scopolamine (SCO) was used to establish an AD model in one study [29] and intracerebroventricular (ICV) injection of Aβ 1-42 was used in two studies [34,35], and the ICV injection of Aβ 1-40 was used in the rest one study [38]. In mice models, three studies adopted APP/PS1 double transgenic mice model [28,33,39], and the rest used SAMP8 mice model as mentioned above [27,32,36,37,40].…”
Section: Model Preparation Methodsmentioning
confidence: 99%
“…e quality assessments of 12 included papers are illustrated in Tables 3 and 4, and the score of the study quality ranged from 2 to 8 out of a total 10 points. Among the 12 studies, only two studies described the specific random method [37,39]. Similarly, only two studies clearly showed that the baseline characteristics had been evaluated or adjusted among the groups before the intervention [35,39], and two studies reported that caregivers or investigators were blinded during the study [29,33], respectively.…”
Section: Study Quality Evaluationmentioning
confidence: 99%
See 3 more Smart Citations